Meningkatkan Kemampuan Sosial Emosional Anak Usia Dini Melalui Metode Role Playing - Siti Fadilah Dwi Febrianti; Finadatul Wahidah (LP3M KH Yazid Karimullah Institute, 2024)
This research explores the role-playing method's effectiveness in improving young children's social-emotional abilities. The role-playing approach was chosen because it can facilitate active and interactive learning, which is believed to strengthen children's social-emotional skills through direct experience in various social scenarios. This research was conducted at RA Ra'iyatul Husnan Bondowoso. The research approach used is qualitative research. The data collection techniques used were interviews, observation, and documentation. The sources used are secondary data and supporting data in the form of journals related to the discussion. Data analysis techniques include data reduction, data display, and data verification. The research results show that early childhood social and emotional abilities can be improved through the role-playing method at RA Ra'iyatul Husnan Bondowoso, which can be done in several stages. The stages are planning, implementation, and evaluation. Planning to improve the social-emotional abilities of early childhood through the role-playing method carried out by RA Ra'iyatul Husnan Bondowoso implemented systematic strategic steps. First, they identified the social-emotional competencies or skills developed in RA Ra'iyatul Husnan Bondowoso's early childhood. For example, the ability to communicate effectively, control oneself and manage emotions, understand and respond to other people's feelings, etc. Second, choose a role or scenario that is suitable for role-playing. After the planning stage had been carried out, teacher RA Ra'iyatul Husnan Bondowoso carried out role-playing activities to improve the social-emotional abilities of young children, which involved concrete steps to achieve goals. During role-playing, teacher RA Ra'iyatul Husnan Bondowoso allows children to interact and explore children's social-emotional responses in a safe and controlled context. The final stage is evaluation. The evaluation methods carried out by RA teacher Ra'iyatul Husnan Bondowoso include Direct Observation, Written Observation, Interviews, and Feedback from RA teacher Ra'iyatul Husnan Bondowoso.